Guideline for the use of immunobiologicals in chronic rhinosinusitis with nasal polyps (CRSwNP) in Brazil - Anselmo-Lima,Wilma T. (2022)
Abstract Introduction Severe uncontrolled chronic rhinosinusitis with nasal polyps has a negative impact on an individual’s quality of life. Therefore, new biologics have emerged for use in specific phenotypes of chronic rhinosinusitis, changing the paradigms of its treatment. Objective To review the current status of biologic treatment indications in chronic rhinosinusitis. Methods The Brazilian Academy of Rhinology brought together different specialists to suggest a course of action, considering its particularities and aspects related to the national reality. Results Of particular interest for decision making will be the identification of subgroups of patients refractory to pre-existing treatment options and the construction of a strategy that improves their quality of life, with the best cost-benefit ratio. Conclusion The use of biologics is a valid option for treatment in more severe cases. This strategy must be better understood and improved in the future, with more studies and greater clinical experience.